The Effect of Islamic Social Reporting, Public Ownership, Number of Meetings, and Education of the Sharia Supervisory Board on Social Performance - Nindi Putrisari; Iwan Fakhruddin; Azmi Fitriati; Dwi Winarni (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the influence of Islamic social reporting, public ownership, the number of Sharia Supervisory Board meetings, and the Sharia Supervisory Board members’ education level on social performance. The population used in this study consisted of Islamic banks from 2017 to 2024. The sampling technique used was purposive, yielding a sample of 116 companies that met the criteria. Empirical testing was conducted using panel data analysis with a fixed-effects model and cluster-standard error correction in STATA to ensure the accuracy of the estimates. The results of this study indicate that the variables public ownership and the Sharia Supervisory Board’s education level have a positive effect on social performance. Meanwhile, the variables Islamic Social Reporting and the number of Sharia Supervisory Board meetings do not affect social performance.